Religious behaviours and commitment among Muslim healthcare workers in Malaysia - Amiruddin, Muhammad Majdy (HTS teologiese studies, 2023)
Religion is among the determinants of human beliefs and values in various societies, shaping people’s behaviours in a range of life aspects, including the workplace. In view of the influence of religion in Malaysia, this issue becomes highly significant. With regard to the profound impact of religion on creating individual and collective behaviours, the present study aims to investigate the effects of religious behaviours (RBs) on organisational commitment (OC) among Malaysian healthcare workers (HCWs) in 2022, by a survey method implemented using standardised questionnaires for data collection. The statistical population comprised of 2500 HCWs from 10 hospitals in Kuala Lumpur, Georgetown and Malacca, Malaysia, selected by the simple random sampling among the Muslim staff. The data analysis was further fulfilled using the AMOS software package for structural equation modelling (SEM). In general, the study results demonstrated a significant and positive relationship between RBs and OC among Malaysian HCWs (p-value = 0.84, t-statistic = 6.50).Contribution: As demonstrated by the study results, it is possible to inspire OC among employees through strengthening RBs and take advantages of the results. Thus, RBs shown by employees can definitely bring positive results to organisations; therefore, OC in Malaysian HCWs improves.